2019
DOI: 10.1186/s12879-019-4459-4
|View full text |Cite
|
Sign up to set email alerts
|

The liver fibrosis index is superior to the APRI and FIB-4 for predicting liver fibrosis in chronic hepatitis B patients in China

Abstract: BackgroundThe purpose of this study was to prospectively investigate the value of real-time ultrasound elastography (RTE) for the diagnosis of liver fibrosis (LF) in patients with chronic hepatitis B (CHB), to correlate the elastography findings with the histologic stage of LF and to compare RTE findings with those from noninvasive tests of LF calculated using laboratory blood parameters.MethodsLiver biopsies, laboratory blood testing, and RTE were performed in 91 patients with CHB. The LF index (LFI) was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…However, there was a slight increase in the percentage of males especially in the severe group, in accordance with studies [30,51,52]. This issue remains controversial, as laboratory analysis showed no significant difference between the studied groups, in accordance with several studies [59][60][61], while other studies contradict our observations [62][63][64][65]. It is possible, though, that the overrepresentation of male subjects relates to HCV infection in general [52] and is not associated with a certain complication or its severity.…”
Section: Discussionsupporting
confidence: 91%
“…However, there was a slight increase in the percentage of males especially in the severe group, in accordance with studies [30,51,52]. This issue remains controversial, as laboratory analysis showed no significant difference between the studied groups, in accordance with several studies [59][60][61], while other studies contradict our observations [62][63][64][65]. It is possible, though, that the overrepresentation of male subjects relates to HCV infection in general [52] and is not associated with a certain complication or its severity.…”
Section: Discussionsupporting
confidence: 91%
“…The WHO recommends AST to platelet ratio index (APRI) calculated according to the formula: APRI = [AST/AST ULN (upper limit of normal) × 100/platelet count (10 9 /l] to estimate the stage Diagnosis and treatment of hepatitis B virus 4 395 of liver fibrosis (WHO 2017b). TE is another noninvasive method; however, due to its limitations such as high cost, inaccurate results with elevated ALT levels, restriction with liver necro-inflammation, and obesity, the WHO recommends the APRI index as a relatively accurate method for predicting advanced liver fibrosis (EASL 2017; WHO 2017b; Huang et al 2019). It has been recommended that 40 IU/ml as ULN value should be used in the APRI formula (WHO 2017b).…”
Section: Biochemical Parameters and Fibrosis Markersmentioning
confidence: 99%
“…Moreover, Huang et al [88] also found that APRI and FIB-4 had a worse predictive ability for identifying significant, advanced LF and cirrhosis than real-time ultrasound elastography in CHB patients in China, with lower sensitivity and accuracy.…”
Section: Disease Markersmentioning
confidence: 99%